Multiple affixation in Portuguese: structural restrictions and processing conditions - Rodrigues, Alexandra Soares (2016)
In recent years, different studies have focused on affix combination (Cf. Hay & Plag 2004; Plag & Baayen 2009; Talamo 2015; Manova & Aronoff 2010). Independently of the difference between the approaches, none of them is dedicated to the analysis of the syntagmatic extension of affixation. This paper aims to analyse the syntagmatic extension of multiple affixation that involves suffixes of Portuguese productive patterns (Rio-Torto et alii 2013). We base our theoretical claims on the analysis of corpora (Reference Corpus of Contemporary Portuguese and Linguateca) and of experiments (lexical decision and recall tasks) with native speakers. Under the perspective of the description of structural constraints, multiple affixation should be possible, as long as structural constraints between affixes are preserved. However, how far does this multiple combination maintain semanticality and grammaticality? Structural constraints predict that words found in corpora such as comercializabilidade and materializabilidade are possible forms. In fact, they are the result of multiple affixation that manifests existent derivational patterns in Portuguese: matériaN>materiN-alADJ>materialADJ-izV>materializ(a)V-velADJ>materializabilADJ-idadeN In spite of the structural well-formedness of the derivatives that result from those patterns, forms such as materializabilidade are considered to be odd by Portuguese speakers. We claim that processing conditions may explain this. In the processing of this kind of words, in a parallel dual-route model (Baayen, Dijkstra & Schreuder 1997; Schreuder & Baayen 1997), the decomposed route would be favoured due to the conjugation of two factors: the very low-frequency of the word and its morphological complexity degree (Niswander-Klement & Pollatsek 2006). However, this route encounters one obstacle: Considering that the goal of morphological analysis made by the speaker/listener is to create meaning (Libben 2015) and that the presence of morphemes in a word expresses a conceptual category (either we consider morphemes as lexical items or as spell-outs of paradigms or rules), the quantity of morphological segments with no referential semantics makes morphological processing difficult. Another obstacle goes against a whole-word processing: Since this combination of suffixes has a very low frequency, it does not correspond to predictable/expected combinations in the speaker’s mind (Hawkins & Blakeslee 2004; Plag & Baayen 2009). Two series of multiple affixation contrast with those cases: I- Words such as ornamentalização, although containing four suffixes (orna-men-al-iz(a)-ção), are accepted. Two reasons may explain this: 1) the first suffix (-ment-) has not a visible derivational role here, since the word ornamento occurs as a concrete and not as an event noun; 2) the sequence -al-iz(a)-ção is very frequent in contemporary Portuguese, which turns it predictable and easily processed (Schreuder & Baayen 1997). II- Multiple affixation in diminutives/augmentatives. Affix combinations that produce nouns/adjectives such as cas-inh-oto-zinho, pequen-in-inho-zinho are frequent and easily processed via the decomposed route. The hypothesis is the following: 1) evaluative affixes have more transparent semantics than suffixes such as -al-, -bil- have; 2) in evaluative formations each one of the suffixes repeats the semantic information of its precedent. In this case, multiple affixation is reinforcing information that is needed to process the word.